Fashion school: media technologies and interdisciplinarity (Research, Society and Development, 2019)
The following article aims to present important concepts for reflection on the teaching of Fashion. Through a bibliographic study, we seek to understand fashion as a social, cultural and personal phenomenon, presenting concepts in order to work on its education focusing on a purpose that goes far beyond the clothes one wears. The objective is to demonstrate the importance of using social media to talk about fashion and also to produce and socialize content in the top fashion design courses. In addition, it was tried to point out to the importance that the teaching in fashion can take into account the interdisciplinarity to work with a purpose that aims at the collective. The use of media technologies as an important feature in the process of fashion education is justified by the fact of them being part of the technological revolution and because its use is due to the interconnection of the entire world. This is one of the foundations of the interdisciplinary globalization of information. It is hoped, through this study, to provide new ways to mobilize learning and to potentialize and stimulate the ideas of the students of the Fashion courses.